Individual‐level Foci of Identification at Work: A Systematic Review of the Literature. (July 2017) - Atewologun, Doyin; Kutzer, Roxanne; Doldor, Elena; Anderson, Deirdre; Sealy, Ruth
Abstract: This paper presents a systematic literature review of individual‐level targets (or foci) of identification, that is, the bases by which one derives a sense of self as a unique being in the context of work. We reviewed 253 articles from over 30 top management journals between 2005 and 2016. In examining foci types, definitions, underpinning theoretical and philosophical assumptions, we catalogue nine categories of individual‐level identification foci (manager, leader, follower, team, organization, occupation‐specific, professional, career and work), finding a dominance of functionalist meta‐theoretical orientations (comprising over half the sample, with interpretivist approaches comprising about a third of studies). Further, we enhance construct clarity in the field; we identify conceptual challenges with extant definitions of key foci, and offer integrative definitions by specifying scope conditions for each identity focus and semantic relationships between various identity foci. We contextualize our discussion of construct clarity to different research orientations in the field and offer possibilities for theoretical developments therein. Third, we offer an integrative framework for positioning work in the field by scope of interest (identity content or context) and identity construction assumptions (stable or evolving), suggesting directions for future research.